Kajian Geologi Dan Statigrafi Daerah Botu dan Sekitarnya, Provinsi Gorontalo - Fauzia Hambali; Sri Maryati; Noviar Akase (Universitas Negeri Gorontalo, 2026)
The research is located in Gorontalo Province, precisely in Dumbo Raya District with coordinates 0°32’24” N and 123°4’32” E. Geologically, the research area is located on the North Arm of Sulawesi Island and belongs to the Southern Mountain Zone. The geological conditions of this region are influenced by complex tectonic activities and intensive geomorphological processes that form diverse landscapes. This research aims to determine the geological conditions including geomorphology, stratigraphy, and geological structures. The method used is field geological mapping supported by secondary data, through observations of rock outcrops, lithological descriptions, and measurements of geological structures. The results show that the geomorphology of the area is dominated by denudational hill units and alluvial plains. The hill units are composed of igneous rocks such as granodiorite and andesite that have experienced weathering and erosion, forming steep slopes. The alluvial plain units are composed of younger loose material. Stratigraphically, the research area consists of granodiorite, andesite, and limestone unit.